Ecophysiological responses to climate change in cicadas - Moriyama, Minoru; Numata, Hideharu (Physiological entomology, 2019)
Cicadas are large hemipteran insects characterized by unique life‐history traits, such as extraordinarily long life cycles, a subterranean/terrestrial habitat transition, xylem sap‐feeding and melodious sound production. These fascinating features of cicadas have attracted much attention in the research fields of physiology and ecology, resulting in an accumulation of knowledge about the underlying mechanisms and their adaptive significance. Although community‐level responses to recent climate change have already been documented for cicada fauna, an understanding of their causal relationships is still at the initial stages. In this review, we summarize current knowledge about environmental adaptations of cicadas to facilitate a deeper understanding of the ecophysiological consequences of climate change. We first outline the diverse responses of cicadas to environmental factors, mainly temperature, and their strategies to cope with naturally fluctuating environments. Then, we discuss the consequence of upcoming climate change by consolidating the current findings. This review highlights the fact that fitness‐relevant activities are fine‐tuned to a species‐specific temperature optimum to achieve habitat segregation among coexisting species, implying that cicada diversity is highly susceptible to climate warming. As a result of their conspicuous large bodies and species‐specific calling songs, cicadas are promising candidates for use as bioindicator species to monitor ecological impacts of climate change. We encourage future works that continuously quantify population‐ and community‐level responses to upcoming climate change, as well as unveil mechanistic links between physiological traits and ecological consequences. Current knowledge about environmental adaptations of cicadas is outlined to facilitate a deeper understanding of the ecophysiological consequences of climate change. The present review highlights the fact that fitness‐relevant activities are fine‐tuned to a species‐specific temperature optimum, implying that cicada diversity is highly susceptible to climate warming. As a result of their conspicuous large bodies and species‐specific calling songs, cicadas are promising candidates for use as bioindicator species to monitor ecological impacts of climate change.